Characterization of the actors in the pasteurized milk chain in the province of Sancti Spíritus, Cuba - Hernández García , Juan E; Ponce de León , Angel Pentón; Nápoles Gómez , José A; Rodríguez Álvarez , Lázaro Pablo; Gómez Brito , Odenys; Gutiérrez Jorge , María de los Ángeles (apm, 2023)
Background: The study of chains at a local level starts from a new configuration constitutes a new working philosophy in the agri-food sector in Cuba. Objective. The aim of the paper is to characterize of the actors in the pasteurized milk chain in four municipalities of Sancti Spíritus province. Methods: It was based on the primary and secondary available information obtained at workshops with the participation of national actors and international experts. The characterization of the actors included the variables described in previous chain studies, the construction of the SWOT Matrix and an action plan. Results: The links of the chain are: Production, collection, processing and marketing. At the primary sector, there are different productive farms with non-governmental dominance. They had a production of approximately 20,000 liters/year, having 20 not specialized female cattle in milk production. Some of the farms use animal traction for milk collection and the industry does this process with tank trucks. The processing link presents technology with limitations and insufficient equipment. The SWOT Matrix revealed that the nutrition is not sufficient and the composition of milk is not good. Besides, the process of collection and the industrial distribution that affect the quality of milk. Conclusions: The characterization of the actors showed that in the primary link with predominance of the non-state sector, but there is low milk production. For the collection of milk, they use animal traction and tanker trucks. Obsolete technologies are found in the processing link, while commercialization actors are limited by hygienic conditions. Key words: Dairy production, dairy cattle, dairy value chain food chain, food access, pasteurized milk (Source: AGROVOC)